Bindi: A Unique Prescription Method for Visually Impaired, Illiterate, and Naïve Patients to Solve the Dependency in Taking Medication - Patel, Swayamprakash (Indian Journal of Pharmacy Practice)
A huge abundance of visually impaired and illiterate people across the world faces the issue of identifying the right medicine from their prescription at the time of consumption. Numerous devices and AI-based tools offer solutions to this challenge. However, none of these methods is universally acceptable, cost-effective, or simple. In this communication, we are sharing a unique method for resolving the VIP problem with little evidence of its effectiveness and acceptability. The Bindi, a common trinket in Indian culture, can present a simple, cost-effective, and universally adoptable solution. (Visual Explanation of Concept is available at the YouTube link: https://youtu.be/hqR3TSi0njA)
Keywords: Visually Impaired Patient; Prescription; Bindi